Edukasi Kebahagiaan Sejati dalam Penyelenggaraan Haji di Tengah Pandemi - Ali Mu’tafi (Pusat Riset dan Inovasi Nasional, 2022)
The research intends to describe true happiness education in organizing Hajj in the midst of a pandemic. The article is the result of qualitative research from literature data, the results of the research show: that happiness is a concept that refers to the positive emotions felt by individuals and the positive activities they like. Even though the Covid-19 pandemic has overshadowed the implementation of the Hajj, everyone in the pilgrimage must develop positive feelings. That way he can feel true happiness. True happiness can be achieved when a person knows himself, knows God, knows the world, and knows the hereafter. It is not something that comes suddenly, but through continuous effort. At least five aspects of the source of true happiness, namely: 1) establishing positive relationships with other people, 2) focusing on something that is done, 3) finding meaning in everyday life, 4) positive emotions, 5) resilience. The implications of research on the need to think positively in response to all circumstances, being the core of the continuity of happiness requires more focused research. Research suggests that Hajj organizers refresh congregations about true happiness.